Animal-ImputeDB: a comprehensive database with multiple animal reference panels for genotype imputation. Issue Volume 48:Issue D1(2020) (4th October 2019) - Yang, Wenqian; Yang, Yanbo; Zhao, Cecheng; Yang, Kun; Wang, Dongyang; Yang, Jiajun; Niu, Xiaohui; Gong, Jing
Abstract: Animal-ImputeDB (http://gong_lab.hzau.edu.cn/Animal_ImputeDB/ ) is a public database with genomic reference panels of 13 animal species for online genotype imputation, genetic variant search, and free download. Genotype imputation is a process of estimating missing genotypes in terms of the haplotypes and genotypes in a reference panel. It can effectively increase the density of single nucleotide polymorphisms (SNPs) and thus can be widely used in large-scale genome-wide association studies (GWASs) using relatively inexpensive and low-density SNP arrays. However, most animals except humans lack high-quality reference panels, which greatly limits the application of genotype imputation in animals. To overcome this limitation, we developed Animal-ImputeDB, which is dedicated to collecting genotype data and whole-genome resequencing data of nonhuman animals from various studies and databases. A computational pipeline was developed to process different types of raw data to construct reference panels. Finally, 13 high-quality reference panels including ∼400 million SNPs from 2265 samples were constructed. In Animal-ImputeDB, an easy-to-use online tool consisting of two popular imputation tools was designed for the purpose of genotype imputation. Collectively, Animal-ImputeDB serves as an important resource for animal genotype imputation and will greatly facilitate research on animal genomic selection and genetic improvement.